Fray Julián Moreno, agustino recoleto mártir: El trovador de Cristo - Santervás, Marciano (Mayéutica, 2024)
The article offers a brief biography of Blessed Julián Moreno, as well as a contextualization of his work. It then presents a cataloguing and literary study of some of his most significant poems, in order to highlight the poetic art of the one who called himself "the Troubadour of Christ." Finally, the article presents the poems of Blessed Julián Moreno, following the thematic order outlined in the first part.